2011
DOI: 10.1080/13662716.2011.561027
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Regulation-Driven Environmental Innovation on Innovation Success and Firm Performance

Abstract: Die Dis cus si on Pape rs die nen einer mög lichst schnel len Ver brei tung von neue ren For schungs arbei ten des ZEW. Die Bei trä ge lie gen in allei ni ger Ver ant wor tung der Auto ren und stel len nicht not wen di ger wei se die Mei nung des ZEW dar.Dis cus si on Papers are inten ded to make results of ZEW research prompt ly avai la ble to other eco no mists in order to encou ra ge dis cus si on and sug gesti ons for revi si ons. The aut hors are sole ly respon si ble for the con tents which do not neces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
118
3
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 286 publications
(130 citation statements)
references
References 28 publications
4
118
3
5
Order By: Relevance
“…Green innovation is defined as "all measures of relevant actors which develop new ideas, behaviours, products and processes, apply or introduce them, and which contribute to a reduction of environmental burdens or to ecologically specified sustainability targets" (Rennings & Rammer, 2011). Corporate implementing green innovation is a complex phenomenon whereas legitimacy theory, stakeholder theory, resource dependence theory, and upper echelons theory (UET) all provide the theoretical basis.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Green innovation is defined as "all measures of relevant actors which develop new ideas, behaviours, products and processes, apply or introduce them, and which contribute to a reduction of environmental burdens or to ecologically specified sustainability targets" (Rennings & Rammer, 2011). Corporate implementing green innovation is a complex phenomenon whereas legitimacy theory, stakeholder theory, resource dependence theory, and upper echelons theory (UET) all provide the theoretical basis.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although there are various types of green innovation and its nature can be technological, organizational, social or institutional, it is commonly divided into green product innovation and green process innovation (Rennings & Rammer, 2011). The former refers to the efforts to improve product quality and safety in order to address environmental issues and to achieve product differentiation by promoting sustainability, which in turn secures competitive advantage (Chen, 2008).…”
Section: Green Innovationmentioning
confidence: 99%
“…In addition, demand-pull and "interface" policies 1 are increasingly recognized to be relevant instruments to stimulate innovativeness and diffusion of technological change (Del Rio Gonzalez 2005;Fischer and Newell 2008;Taylor 2008;Popp 2011;Rennings and Rammer 2011;Horbach, Oltra, and Belin 2013). Although there are examples of innovations developed in response to foreign regulations, environmentally sound inventions are more likely to respond to domestic environmental policies (Lanjouw and Mody 1996), particularly as far as new energy technologies are concerned (Popp 2006).…”
Section: Introductionmentioning
confidence: 97%
“…Researchers have identified that different regulatory policies have a varied effect on the innovation performance of firms (Rennings and Rammer, ; Blind, ). Economic regulations focused on improving the growth of an industry positively impact innovation (Amable et al ., ; Ramanathan et al ., ; Clarke, ; Lee et al ., ; Rennings and Rammer, ), while those intended to protect an industry negatively impact innovation (Grabowski et al ., ; Marcus, ; Birnbaum, 1984; Smith and Grimm, ; de Bijl and Peitz, ). Bourreaua and Doğan ( ) and Keyhani et al .…”
Section: Theory and Hypothesesmentioning
confidence: 99%